The effect of leader damage on lodgepole pine site tree height growth - Gord Nigh (The Forestry Chronicle)
Site index is an important parameter in forest management. Selecting good site trees is critical for both developing and applying models to estimate site index. Along with other characteristics, site trees must be free of damage so that the growth of the tree reflects the potential productivity of the site. Detecting and avoiding leader damage in site trees is very difficult because radial stem growth eventually hides the damage, even in young trees. This project quantifies the loss in height growth due to hidden leader damage. Thirty-seven lodgepole pine (Pinus contorta var. latifolia) site trees were destructively sampled. Annual height growth was measured and incidents of leader damage noted. Height growth was modelled in a mixed-effects framework and allowed for growth reductions due to leader damage. Height growth was reduced on average by 35% in the year the damage occurred and by 15% in the year after the damage event. Height growth returned to normal in subsequent years. The effect of leader damage on the estimated site index depends on when and how many damage events occur, and when the site index estimate is made. For a tree with a site index of 20 m at base age 50 years at breast height that has leader damage at age 8, a reduction in the estimated site index of 0.59 m and 0.31 m can be expected when site index is estimated at ages 10 and 25, respectively.